Three essays on personality and net worth - Nabeshima, George (Kansas State University, 2014)
This dissertation consists of three studies exploring the relationship between personality and wealth related variables. The psychological type theory was used as the theoretical framework for the first two studies, while the doctrine of interactionism was used in the third study. All three studies utilized data from the 2010 panel of the Health and Retirement Study (HRS). The first study examined the relationship between personality traits and net worth. Linear regression results identified the extroversion and conscientiousness traits as being positively associated with net worth. Furthermore, the agreeableness trait was negatively associated with net worth. The second study explored the relationship between personality preference and stock ownership. This study’s logistic regression results identified the preference for high openness and high neuroticism as significant and positively associated with stock ownership. A high agreeableness preference was significant and negatively associated with stock ownership. The focus of the third study examined how net worth and income mediated the association between personality and life satisfaction. Regression results from this study identified net worth as being a significant mediating variable in the association between the conscientiousness trait and life satisfaction levels. However, income, in addition to net worth, was also a significant mediating variable when the extroversion and neuroticism traits were used to represent personality trait variables. Results from the three studies identified significant associations between personality traits and components of net worth. These findings contribute to the financial planning field by providing useful information in regards to how mental preferences expressed outwardly though personality traits are related to wealth related variables and life satisfaction. Financial planning practitioners can apply these findings to formulate strategies to assist people grow their wealth levels.
Keywords: Personality; Money; Happiness; Financial Planning; Investing; Home Economics (0386); Individual & Family Studies (0628); Personality Psychology (0625)